Exposure to increased levels of estradiol during development can have long-term effects on the response to undernutrition in female rats. (8th November 2016) - Carrillo, B.; Collado, P.; Díaz, F.; Chowen, J. A.; Pinos, H.
Abstract : Objectives : Undernutrition during development alters the expression of peptides that control energy expenditure and feeding behavior. Estrogens can also modulate these peptides. Here, we analyze whether the early postnatal administration of estradiol modulates the effects of undernutrition on neuroendocrine parameters in adult female Wistar rats. Methods : Control rats were fed a control diet. Undernourished pups were submitted to a restricted diet with half of the undernourished rats receiving 0.4 mg/kg s.c. of estradiol benzoate (EB) from postnatal day (P) 6 until P13. Quantitative real-time polymerase chain reaction was performed to determine expression in the hypothalamus of agouti-related peptide (AgRP), proopiomelanocortin (POMC), neuropeptide Y (NPY), and cocaine- and amphetamine-regulated transcript. Plasma estradiol, testosterone, and adiponectin levels were measured by enzyme-linked immunosorbent assay. Total and acylated ghrelin levels were measured in plasma by radioimmunoassay. Insulin and leptin were measured by mulitplex immunoassays. Results : Undernourishment decreased body weight, fat mass, plasma leptin and insulin levels, and hypothalamic POMC mRNA levels. An increase in orexigenic signals AgRP and NPY mRNA levels, and in plasma adiponectin levels were found in undernourished animals. Early postnatal treatment with EB to undernourished female rats reversed the effects of undernutrition on adult hypothalamic POMC mRNA levels. In addition, neonatal EB treatment to undernourished females significantly decreased adult plasma testosterone, estradiol, and acylated ghrelin levels. Discussion : Our results suggest that increased estradiol during a critical period of development has the capacity to modulate the alterations that undernutrition produces on energy metabolism.